Development and performance evaluation of a novel scintillation-based active shielding gamma probe - Kolcu, O. B.; Yetkin, T.; Zengin, A. T.; Iren, E.; Gunay, E. C. (SPRINGER, 2024)
The gamma probe is a commonly used detector for localizing sentinel lymph nodes after the injection of radiopharmaceuticals. In recent years, studies have focused on improving the features of gamma probes to achieve more consistent localization of the radiotracer uptake. As part of this effort, a novel gamma probe prototype based on an active shielding was developed, and its characteristics, including sensitivity, resolution and shielding effectiveness, were determined. The prototype integrates trapezoidal-shaped bismuth germanate (BGO) array coupled with a silicon photomultiplier (SiPM) array, accompanied by dedicated electronics and software for stand alone usage. We conducted a thorough characterization, validating experimental observations through Monte Carlo simulations using the GEANT4 simulation package. In scattering environment, with a probe-source distance of 30 mm, the experimental results show that the detector sensitivity is 120 +/- 5\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$120\pm 5$$\end{document} cps/MBq, and the spatial and angular resolutions, in terms of full width at half maximum (FWHM), are 44.8 +/- 1.3\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$44.8\pm 1.3$$\end{document} mm and 87.3 +/- 1.5 degrees\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$87.3\pm 1.5 {\circ }$$\end{document}, respectively. The shielding effectiveness of the probe was determined to be greater than 95%\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\%$$\end{document}. The prototype with active shielding was found to have comparable performance to conventional gamma probes.
Keywords: Gamma probes; Intra-operative probes; Active shielding; Sentinel lymph node; Engineering; Radiology, Nuclear Medicine & Medical Imaging